Water sanitation problem in Pakistan: A review on disease prevalence, strategies for treatment and prevention. (October 2022) - Qamar, Khulud; Nchasi, Goodluck; Mirha, Hania Tul; Siddiqui, Javeria Arif; Jahangir, Kainat; Shaeen, Sean Kaisser; Islam, Zarmina; Essar, Mohammad Yasir
Abstract: The global water crisis is expected to worsen if urgent action is not taken in making sustainable amends. This applies to Pakistan as the entire country suffers massively from poor water sanitation. Waterborne diseases are rising exponentially attributed to rise in microbial infestations, trace elements and drug toxicity in many water bodies of Pakistan. Treatment and prevention strategies must be implemented through national authorities and at the individual level. Awareness on use of clean water must be emphasized and proper administration on water management policies should be implemented. Immediate and active sustainability for water resources can ensure a safer future for Pakistan. Highlights: Water Sanitation has been a problem all over Pakistan. The current situation has shown that most rural areas and some urban areas suffer due to the unclean water supply, which progresses in many diseases. This paper combines many methods of preventing waterborne diseases and treating the water bodies to make it free from contaminants.